Whole-Genome Identification and Expression Pattern of the Vicinal Oxygen Chelate Family in Rapeseed (Brassica napus L.) - Liang, Yu; Wan, Neng; Cheng, Zao; Mo, Yufeng; Liu, Baolin; Liu, Hui; Raboanatahiry, Nadia; Yin, Yongtai; Li, Maoteng (Frontiers in Plant Science, 2017)
Vicinal oxygen chelate proteins (VOC) are members of the metalloenzyme superfamily, which plays roles in many biological reactions. Some members of the VOC superfamily have been systematically characterized but not in Brassica napus. In this study, 38 VOC genes were identified based on their conserved domains. The present results revealed that most of the BnaVOC genes have few introns, and all contained the typical VOC structure of βαβββ modules. The BnaVOC genes are distributed unevenly across 15 chromosomes in B. napus and occur as gene clusters on chromosomes C5 and A6. The synteny and phylogenetic analyses revealed that the VOC gene family is a consequence of mesopolyploidy events that occurred in Brassica evolution, and whole-genome duplication and segmental duplication played a major role in the expansion of the BnaVOC gene family. The expression profile analysis indicated that the expression of most BnaVOCs was increased in the leaves and late stage seeds. Further results indicated that seeds of B. napus with a high oil content show higher expression levels under drought stress conditions, suggesting that BnaVOCs not only respond to abiotic stress but may also affect lipid metabolism in drought stress. This present study provides a comprehensive overview of the VOC gene family and provides new insights into their biological function in B. napus evolution.